PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS IV SDN 105 SANGKALA KABUPATEN BULUKUMBA - Sri Dewi Idil Fitri; Sukmawati; Haerul Syam (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The application of the Discovery Learning model is one of the effectiveapproaches to solving problems in the learning process. The Discovery Learningmodel gives students the responsibility to solve problems independently and withtheir group friends, making them more active. The research problem is whetherthere is an influence of using the Discovery Learning model on the mathematicslearning outcomes of fourth-grade students at SDN 105 Sangkala, BulukumbaRegency. This study uses a quantitative approach with an experimental researchtype where the design used is a pre-experimental design in a one-group pretest-posttest format. The sample in this study was selected intentionally usingpurposive sampling techniques to represent the population. The research sampleconsisted of 24 students from class IV B 105 Sangkala, Bulukumba Regency. Thedata collection techniques used are observation sheets, written tests, anddocumentation. The data analysis techniques used are descriptive analysistechniques, which include descriptive statistics and N-Gain tests, as well asinferential analysis techniques, including normality tests and hypothesis tests. Theresults of the inferential statistical analysis conducted with the t-test on the posttestdata analyzed using SPSS version 27.0 for Windows. The t-test consists of themathematics learning outcomes in the experimental class. This is demonstrated bythe hypothesis testing sig. (2-tailed) < α. Consequently, due to the value, H0 isrejected and H1 is accepted 0.001 > 0.05. Furthermore, the data shows that theaverage post-test scores of the experimental class ranged from a highest of 100 toa lowest of 60. Therefore, it can be concluded that the level of student learning isinfluenced by the application of the Discovery Learning model in mathematicseducation.